BEYOND THE LINES: EXPLORING THE IMPACT OF ADVERSE CHILDHOOD EXPERIENCES ON NCAA STUDENT-ATHLETE HEALTH - Brown, Braden J (East Carolina University, 2019)
National Collegiate Athletic Association (NCAA) student-athletes are faced with unique stressors that put them at increased risk for various biopsychosocial-spiritual (BPSS) health concerns. Additionally, given the high prevalence of adverse childhood experiences (ACEs) in diverse populations, it is likely that many student-athletes are also coping with challenges stemming from negative childhood events. Despite a substantial amount of evidence linking ACEs to deleterious BPSS health outcomes in both young adult and adult populations, little is known about the impact of ACEs on the overall health of student-athletes. This dissertation is comprised of the following six chapters: (a) an introduction to the dissertation, (b) a literature review exploring BPSS health concerns experienced by NCAA student-athletes and the impact of ACEs on health outcomes, (c) a systematic review examining the effectiveness of interventions being used to improve BPSS health outcomes among student-athletes, (d) a proposed methodology for the original research study, (e) an original research study exploring the interplay between ACEs and BPSS health outcomes among Division I, II, and III NCAA student-athletes (N = 477) who represented 20 sports across 53 universities, and (f) a series of implications and recommendations for researchers, clinicians, and NCAA athletics personnel.
Keywords: NCAA; Student-Athletes; Adverse Childhood Experiences, Biopsychosocial-Spiritual; College athletes--Mental health; Child abuse; Psychobiology